Identification and verification of autophagy-related gene signatures and their association with immune infiltration and drug responsiveness in epilepsy - He, Han-han; Zhang, Xiao-ge; Chen, Fen-fang (Frontiers in Neurology, 2025)
BackgroundEpilepsy, a common neurological disorder, is characterized by susceptibility to recurrent seizures. Increasing evidence suggests that autophagy plays a crucial role in the initiation and progression of epilepsy. However, the precise mechanisms by which autophagy deficiencies involved in epileptogenesis are still not fully understood.MethodsTwo datasets of epilepsy (GSE143272 and GSE256068) were downloaded from the Gene Expression Omnibus (GEO) database. Differential expression genes (DEGs) analysis and weighted gene co-expression network analysis (WGCNA) were employed to screen for autophagy related differential expression genes (ARDEGs) in GSE143272 database. Subsequently, protein–protein interaction, transcription factors and miRNAs networks were constructed. Additionally, the functional enrichment analysis of Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) were applied. The hub ARDEGs were identified through CytoHubba, followed by the LASSO analysis. The Immune Cell Abundance Identifier (ImmuCellAI) was used to estimate peripheral immune cells abundance of epilepsy. Furthermore, the expression level of hub ARDEGs were detected in patients treated with different epilepsy monotherapies to explore the role of autophagy in the responsiveness of antiepileptic drug therapy. Finally, the expression level of hub ARDEGs were further validated in hippocampus of GSE256068 to enhance the reliability of the results.ResultsTwenty ARDEGs in epilepsy were screened out by integrating DEGs and WGCNA analysis. KEGG enrichment analysis showed that the ARDEGs in epilepsy were not only involved in the autophagy, but also apoptosis, the NOD-like receptor signaling pathway, the neurotrophin signaling pathway, etc. Four hub ARDEGs (PIK3R1, TRIM21, TRIM22, and ITPR3) were screened through integrating CytoHubba plug and LASSO analysis. The immune infiltration analysis showed that there was a significantly increased abundance of macrophages and a decreased abundance of CD4 and CD8 T cells, including Tr1, nTreg, Tfh, CD8 naïve, cytotoxic T cells and effector memory T cells in the epilepsy group. Furthermore, the hub ARDEGs were significantly correlated with the abundance of differential immune cells. In expression level validation and anti-epileptic drug responsiveness analysis, PIK3R1 and ITPR3 had significant differences in the hippocampus of patients with epilepsy. PIK3R1 expression level was found to be related with carbamazepine resistance.ConclusionThis study elucidated the autophagy-related gene signatures in epilepsy and clarified their association with immune infiltration and anti-epileptic drug responsiveness, providing a novel target for future therapeutic interventions and disease markers in epilepsy.